The Specialized Language of Commerce in Spanish: Design of a Corpus for its Diachronic Study - De Beni, Matteo (2020)
The purpose of this article is to present the design features of the DIACOM corpus, a tool for the study of the field-specific lexis related to trade and commerce in the Spanish and French language. This study, carried out by the Department of Foreign Languages and Literatures of the University of Verona (Italy) within the framework of a government-funded project, aims at developing the field of Digital Humanities and specifically its application in linguistic and philological research. The paper addresses the issues related to designing the Spanish subcorpus, particularly the ones which have proved especially problematic in the building of a diachronic corpus within the area taken into account.